The compliance of ecological design on public buildings on the university campus environment in Malaysia - Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (IACSIT Press, 2015)
The concern for the natural and built environment has become crucial in relation to the concept of sustainable development. Literatures show that the ecological design (ED) concept has produced positive results in supporting the achievement of sustainable development, though it faces many challenges amongst public and other stakeholders of its importance towards a green environment. This research attempts to seek the level of the ED compliance in the Putra University of Malaysia campus. The objectives are: (1) to determine the present ED features that are being practised in education building in the campus; and (2) to identify the level of compliance of ED variables in the campus. An observation survey of 23 selected buildings within the campus was conducted, based on a set of pre-determined five variables and its sub-variables in determining the level of compliance to ED. The results demonstrated that the level was relatively moderate, and many buildings failed to comply with some variables of ED. It is concluded that the research has met its outlined objectives in which the findings demonstrate that the level of ED compliance in the campus can be considered as moderate.